Implementation of 5S for Safety and Worker Productivity at Expedition Services Companies (A Study in the JNE Express Operations Department) - Syamila, Ana Islamiyah (Universitas Nahdlatul Ulama Surabaya, 2025)
Delays in delivering goods to consumers via expeditions continue to pose a challenge, leading to inaccuracies in the established delivery schedule. This issue is closely related to the productivity of couriers and warehouse staff involved in the delivery process. 5S Safety (Sort, set in order, Shine, Standardize, Sustain, and Safety) is recognized as a factor influencing employee productivity. This study examines the relationship between the implementation of 5S Safety and the work productivity of operational workers at JNE Express Jember. This research was designed as a quantitative analytic study with a cross-sectional approach. It was conducted at JNE Express Jember in December from October 2022 to May 2023 and involved 74 operational workers as respondents. Respondents were selected using the proportionate random sampling method. Research data were gathered through interviews based on a questionnaire. The data were analyzed univariately and bivariately using the Spearman test, and the results were presented in tabular form accompanied by narrative explanations. This study's findings indicate no discernible relationship between individual characteristics (age, education level, and years of service), training, work motivation, and the implementation of 5S Safety concerning work productivity among JNE Express Jember’s operational workers. Management needs to monitor and evaluate the implementation of 5S Safety, enhance the training provided, and offer motivation and recognition to employees who perform their duties effectively. Employees are also encouraged to take responsibility for diligently applying 5S Safety practices and utilizing the skills and knowledge acquired from their training in their daily work. Keywords: 5S Safety, courier, expedition, work productivity